Calculations of the thermophysical properties of low‐temperature Pb plasma at low densities. Issue 10 (12th May 2021) - Apfelbaum, Evgeny M.
Abstract: The pressure, internal energy, and electronic transport coefficients of low‐temperature Pb plasma were calculated at the temperatures 10–100 kK by means of an earlier developed model (E. M. Apfelbaum, Contrib. Plasma Phys. 2019, 59, e201800148). The plasma composition and thermodynamics were obtained using a chemical approach. The electronic transport coefficients were calculated within the relaxation time approximation with the new accurate momentum transfer cross‐section electron‐atom. The results of the present calculations have been compared with the new measurement data, obtained at relatively low densities, reaching 0.125 of the value in solid state, which corresponds to the area, where the model can be applied correctly. The good agreement between the calculations and measurements was obtained for both the pressure and the electrical conductivity.